1‐nm Si Patterning: Patterning Si at the 1 nm Length Scale with Aberration‐Corrected Electron‐Beam Lithography: Tuning of Plasmonic Properties by Design (Adv. Funct. Mater. 52/2019). (23rd December 2019) - Manfrinato, Vitor R.; Camino, Fernando E.; Stein, Aaron; Zhang, Lihua; Lu, Ming; Stach, Eric A.; Black, Charles T.
Abstract : In article number 1903429, Vitor R. Manfrinato, Fernando E. Camino, and co‐workers achieve 1‐nm resolution Si patterning using aberration‐corrected electron‐beam lithography (AC‐EBL) and reactive ion etching, techniques compatible with Si technology processes, resulting in features with a line edge roughness of 1 nm. AC‐EBL is also used to tune the Si volume plasmon energy as a function of nanostructure geometry, demonstrating control of electro‐optical properties of nanostructures by design.